2018
DOI: 10.3389/fchem.2018.00627
|View full text |Cite
|
Sign up to set email alerts
|

Biochemodynamic Features of Metal Ions Bound by Micro- and Nano-Plastics in Aquatic Media

Abstract: A simple model, based on spherical geometry, is applied to the description of release kinetics of metal species from nano- and micro-plastic particles. Compiled literature data show that the effective diffusion coefficients, Deff, for metal species within plastic polymer bodies are many orders of magnitude lower than those applicable for metal ions in bulk aqueous media. Consequently, diffusion of metal ions in the aqueous medium is much faster than that within the body of the plastic particle. So long as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 90 publications
(121 reference statements)
2
30
0
1
Order By: Relevance
“…27 However, release is more likely from environmental PVC that has weathered and become micronised and that is exposed to physico-chemical conditions favouring the dissolution of inorganic compounds. 28,50,51 The inadvertent ingestion and digestion of microplastics by aquatic organisms and birds provides a means by which these conditions are met, and examinations of the gastro-intestinal tracts of bivalves 42,[52][53][54][55][56] have conrmed that PVC particles are oen present. As part of previous research, selected consumer and environmental samples reported in the current paper were micronised (mm-sized) to study the release of metals from PVC (and other plastics) in simulated digestive uids.…”
Section: Differences In Pvc Abundance Between Consumer and Environmental Samplesmentioning
confidence: 99%
“…27 However, release is more likely from environmental PVC that has weathered and become micronised and that is exposed to physico-chemical conditions favouring the dissolution of inorganic compounds. 28,50,51 The inadvertent ingestion and digestion of microplastics by aquatic organisms and birds provides a means by which these conditions are met, and examinations of the gastro-intestinal tracts of bivalves 42,[52][53][54][55][56] have conrmed that PVC particles are oen present. As part of previous research, selected consumer and environmental samples reported in the current paper were micronised (mm-sized) to study the release of metals from PVC (and other plastics) in simulated digestive uids.…”
Section: Differences In Pvc Abundance Between Consumer and Environmental Samplesmentioning
confidence: 99%
“…Previous studies revealed that diffusion behavior of polymers is influenced by several factors for example, polymer morphology, polymer density, molecular weight distribution, crystallinity, glass transition temperature, or polymer melting temperature. [27,28,[32][33][34] Here, we used an imaging mass spectrometry based method as a tool to analyze chemical metal ion diffusion in polymers. [35] Therefore a cryo-approach was established successfully to stop the diffusion process for the subsequent analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Though polymers were considered to be inert towards metals in the past [97], great attention has recently been paid to better understanding the interaction between heavy metals and microplastics [98][99][100][101][102][103][104][105][106][107][108].…”
Section: Heavy Metalsmentioning
confidence: 99%